A qualitative inquiry of parents' observations of their children's mental health needs during the COVID-19 pandemic. Issue 2 (3rd April 2022) - Barth, Alexandra M.; Meinert, Allison C.; Zopatti, Katherine L.; Mathai, David; Leong, Alicia W.; Dickinson, Emily M.; Goodman, Wayne K.; Shah, Asim A.; Schneider, Sophie C.; Storch, Eric A.
ABSTRACT: Given that children and adolescents are at critical periods of development, they may be particularly vulnerable to the effects of the COVID-19 pandemic. Using a descriptive phenomenological approach, 71 parents' observations of their child's mental health difficulties were explored. Parents sought out treatment because their children were experiencing significant distress. Data used were transcribed from baseline questionnaires and therapy summaries. Data analysis revealed three themes: emotion regulation difficulties, hypervigilance, and despair. The search for strategies and tailored interventions to help mitigate the potential harmful and long-term mental health impacts of the pandemic should be at the forefront of research and clinical practice.